Subelliptic Harmonic Maps with Values in Metric Spaces of Nonpositive Curvature (Communications in Mathematical Research, 2022)
We prove the Hölder continuity of a harmonic map from a domain ofa sub-Riemannian manifold into a locally compact manifold with nonpositivecurvature, and more generally into a non-positively curved metric space in theAlexandrov sense.